2014
DOI: 10.4314/ejhs.v24i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension and Associated Factors in Bedele Town, Southwest Ethiopia

Abstract: BackgroundHypertension is the leading cause of death in the world and is the commonest cause for outpatient visits to physicians. The objective of this study was to assess the prevalence of hypertension and its risk factors among adults in Bedele Town, South-west Ethiopia.MethodA community-based cross-sectional survey was conducted by interviewing participants regarding their socio-demographic characteristics, history of hypertension, its risk factors and knowledge of its complications and treatment. Measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
84
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(132 citation statements)
references
References 18 publications
41
84
6
1
Order By: Relevance
“…This result was comparable with a community based study conducted in Mekelle town, 11% [9]. This prevalence estimate in this study is much lower than those reported from most urban communities of Sub-Saharan Africa (23.7-33.3%), Gondar (28.3%), Addis Ababa (30%), and South Ethiopia (16.9%) [4,7,10,13] respectively. This discrepancy may be explained in two ways; First, the age difference in the study populations (>20 years in our case while in other studies age of participants ranges between 25-65 years).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This result was comparable with a community based study conducted in Mekelle town, 11% [9]. This prevalence estimate in this study is much lower than those reported from most urban communities of Sub-Saharan Africa (23.7-33.3%), Gondar (28.3%), Addis Ababa (30%), and South Ethiopia (16.9%) [4,7,10,13] respectively. This discrepancy may be explained in two ways; First, the age difference in the study populations (>20 years in our case while in other studies age of participants ranges between 25-65 years).…”
Section: Discussionsupporting
confidence: 84%
“…The overall prevalence of hypertension was 13 Slightly more than one in every seven adults aged 30 years or older had hypertension in Jigjiga town (13.3%). This result was comparable with a community based study conducted in Mekelle town, 11% [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, about 62% of cerebrovascular diseases and 49% of ischemic heart disease are attributable to elevated blood pressure (BP) [8]. In developing countries, its morbidity and mortality are increasing due to a change in life style.…”
Section: Introductionmentioning
confidence: 99%
“…Vale destacar que a identificação precoce dos riscos que levam a hipertensão arterial auxilia na implementação de estratégias terapêuticas para prevenir complicações decorrentes da doença, como por exemplo, as doenças cardiovasculares e os acidentes vasculares (BONSA, GUDINA, HAJITO, 2014;EZZATI et al, 2003).…”
Section: Introducãounclassified